1966
DOI: 10.1113/jphysiol.1966.sp007994
|View full text |Cite
|
Sign up to set email alerts
|

Release of vasopressin and oxytocin from isolated pituitary glands of adult and new‐born rats

Abstract: SUMMARY1. Pituitary glands of adult rats of both sexes, of lactating female and of new-born rats, incubated in a Locke solution, release both oxytocin and vasopressin. The amount of hormones released, during a measured period of incubation, is related to the actual hormone content of the gland.2. Increasing the concentration of KCI in the incubation medium, with CaO12 present and in concentration of at least 2-2 mm, produces an enhanced release of both hormones from pituitary glands of adults, but does not aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1967
1967
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…In the adrenal medulla, the direct cause of depolarization of the chromaffin cell is not the propagated impulse but acetylcholine (Ach) released from the secretory nerve terminal (DOUGLAS et al, 1967). But it was confirmed that the neurohypophysial hormone could not be released by Ach applied to the isolated pituitary gland (DOUGLAS and POISNER, 1964;DICKER, 1966;DANIEL and LEDERIS, 1967). Therefore, it is likely that the change in permeability to Ca++ at the terminal of neurosecretory fiber in the neurohypophysis is caused by the arrival of the impulse itself.…”
Section: Imentioning
confidence: 99%
“…In the adrenal medulla, the direct cause of depolarization of the chromaffin cell is not the propagated impulse but acetylcholine (Ach) released from the secretory nerve terminal (DOUGLAS et al, 1967). But it was confirmed that the neurohypophysial hormone could not be released by Ach applied to the isolated pituitary gland (DOUGLAS and POISNER, 1964;DICKER, 1966;DANIEL and LEDERIS, 1967). Therefore, it is likely that the change in permeability to Ca++ at the terminal of neurosecretory fiber in the neurohypophysis is caused by the arrival of the impulse itself.…”
Section: Imentioning
confidence: 99%
“…However, membrane depolarization in the nerve terminals, by means of increased concentrations of potassium and calcium in the incubation medium, causes a pronounced release of vasopressin and oxytocin from isolated neural lobes (Douglas, 1963; Lederis, 1963;Douglas & Poisner 1964a; Dicker, 1966). The role of acetylcholine in the depolarization of the neural lobe nerve terminals is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Although someinformation on the release of vasopressin from the isolated pituitary gland has been submitted (DOUGLAS and POISNER,1964a,b;DOUGLAS and ISHIDA,1965;ISHIDA,1967),little has been written on the release of oxytocin.Of course,plenty of studies have been carried out on the neural control of oxytocin secretion or the action of oxytocin on the uterine muscle (see"oxytocin"Ed.by CALDEYRO-BARCIA and HELLER,1961),but the onlyinformation concerning the release of oxytocin at the nerve terminal was submitted by DICKER(1966),describing that external Ca++is necessary for the release of oxytocin.…”
mentioning
confidence: 99%